Do nonprofessional investors value the assurance of integrated reports? Exploratory evidence. Issue 1 (February 2022) - Gerwanski, Jannik; Velte, Patrick; Mechtel, Mario
Abstract: Using an experimental design, this explorative study provides unique empirical evidence of the effects of an integrated reporting assurance (IRA) on nonprofessional investors' (NPIs) financial decision-making in a laboratory experiment. For this purpose, two independent experiments were carried out, one relying on a sample of Master's students, and one focusing on managers of large corporations. In line with our agency theoretical reasoning, we find that students value an IRA positively, evidenced through significantly higher investments, while, contrary to expectations, an IRA has the opposite effect for managers. The results reveal that, dependent on the empirical model, an IRA has either no, or even an investment-decreasing, impact on executives. In order to assess the sense-making process underlying this conundrum, subsequent interviews with the managers were carried out which revealed three dimensions that shape practitioners' critical attitudes towards assurance engagements. First, managers expressed a general disbelief in the decision usefulness of integrated reporting (IR) to (nonprofessional) investors. Second, interlocutors referred to negative practical experiences with audit and assurance engagements and had technical doubts specific to IRA. Third, managers voiced emotional caveats regarding the audit and assurance profession. These findings indicate a prevailing divergence between the extolled theoretical contribution of an IRA to report credibility and its actual nature in practice. In the further course of the investigation, we also find that the assurance provider (Big 4 auditor versus specialized consultant) does not affect investment decisions, but that a higher assurance level leverages investments among students. The results of this study add to the growing, albeit still small, IRA research body and deliver valuable insights for research, regulators, and practice. Highlights: Experiment: integrated reporting (IR) assurance and nonprofessional investors. IR assurance and higher assurance levels increase Masters students' investments. Unexpectedly, IR assurance rather decreases investments among managers. Subsequent interviews reveal three reasons for managers' dismissive attitude.